Financial Reporting is the Conceptual Basis of International Standards (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article briefly covers how Uzbekistan adopted international standards during the late Renaissance, conceptual framework, financial accounting elements and their importance in practice, main content. The article cites conclusions and suggestions on the topic.